A brief review on plant fibres composites: Extraction, chemical treatment and fibre orientation. (2022) - Aravinth, K.; Ramakrishnan, T.; Tamilarasan, V.D.; Veeramanikandan, K.
Abstract: In the current era of a fast-moving world people were slowly destroying the beauty of nature by consuming non-degradable materials in their day to day life. If this continues the nature of the terrain will completely get extinguished. To protect this type of destructive revolution researchers and scientists were started working on biodegradable materials. In this developing phase, natural fibre composites were leading front to create a bio-degradable revolution. Already many researchers were developed various natural fibre composites from natural resources available around us. In this review article, a brief knowledge about various natural fibre extracting methods, different types of chemical treatment before reinforcement and fibre orientation is the important aspect in deciding the mechanical characteristics of natural fibre reinforced composite, which was also discussed in this paper.